THE UNSAID AS MEANING IN LITERARY TRANSLATION - Firuzabonu Bekmurodova Normurodovna (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This article examines challenges of conveying implicit meaning in literary translation. Using Utkir Hoshimov’s novel, it explores implicature, presupposition, and cultural codes, emphasizing risks of over-explicitation and its impact on literary aesthetics and reader interpretation.